173k views
3 votes
y=c1e^x+c2e^−x is a two-parameter family of solutions of the second order differential equation y′′−y=0. Find a solution of the second order initial value problem with initial conditions y(−1)=3,y′(−1)=−3

User Shivam Roy
by
5.2k points

1 Answer

0 votes

The general form of a solution of the differential equation is already provided for us:


y(x) = c_1 \textrm{e}^x + c_2\textrm{e}^(-x),

where
c_1, c_2 \in \mathbb{R}. We now want to find a solution
y such that
y(-1)=3 and
y'(-1)=-3. Therefore, all we need to do is find the constants
c_1 and
c_2 that satisfy the initial conditions. For the first condition, we have:
y(-1)=3 \iff c_1 \textrm{e}^(-1) + c_2 \textrm{e}^(-(-1)) = 3 \iff c_1\textrm{e}^(-1) + c_2\textrm{e} = 3.

For the second condition, we need to find the derivative
y' first. In this case, we have:


y'(x) = \left(c_1\textrm{e}^x + c_2\textrm{e}^(-x)\right)' = c_1\textrm{e}^x - c_2\textrm{e}^(-x).

Therefore:


y'(-1) = -3 \iff c_1\textrm{e}^(-1) - c_2\textrm{e}^(-(-1)) = -3 \iff c_1\textrm{e}^(-1) - c_2\textrm{e} = -3.

This means that we must solve the following system of equations:


\begin{cases}c_1\textrm{e}^(-1) + c_2\textrm{e} = 3 \\ c_1\textrm{e}^(-1) - c_2\textrm{e} = -3\end{cases}.

If we add the equations above, we get:


\left(c_1\textrm{e}^(-1) + c_2\textrm{e}\right) + \left(c_1\textrm{e}^(-1) - c_2\textrm{e} \right) = 3-3 \iff 2c_1\textrm{e}^(-1) = 0 \iff c_1 = 0.

If we now substitute
c_1 = 0 into either of the equations in the system, we get:


c_2 \textrm{e} = 3 \iff c_2 = \frac{3}{\textrm{e}} = 3\textrm{e}^(-1.)

This means that the solution obeying the initial conditions is:


\boxed{y(x) = 3\textrm{e}^(-1) * \textrm{e}^(-x) = 3\textrm{e}^(-x-1)}.

Indeed, we can see that:


y(-1) = 3\textrm{e}^(-(-1) -1) = 3\textrm{e}^(1-1) = 3\textrm{e}^0 = 3


y'(x) =-3\textrm{e}^(-x-1) \implies y'(-1) = -3\textrm{e}^(-(-1)-1) = -3\textrm{e}^(1-1) = -3\textrm{e}^0 = -3,

which do correspond to the desired initial conditions.

User Pius Raeder
by
5.3k points